Causal effects and metabolites mediators between immune cell and risk of breast cancer: a Mendelian randomization study - Ming, Ruijie; Wu, Huan; Liu, Hong; Zhan, Fangbiao; Qiu, Xingan; Ji, Ming (Frontiers in Genetics, 2024)
The incidence and mortality of female breast cancer remain high, and the immune microenvironment of breast cancer has undergone significant alterations.However, the impact of blood immune cell levels on the risk of breast cancer is not fully understood. Therefor this study aims to investigate the causal relationship between blood immune cell levels and the risk of breast cancer.Methods: A Mendelian randomization (MR) analysis was employed to assess the causal relationship between immune cells and the risk of breast cancer, as along with their potential mediating factors. Genetic statistics of metabolites breast cancer and immune cells were obtained from the GWAS Catalog, while the Genome-wide association studies (GWAS) statistics of breast cancer were extracted from the UK biobank. Two-sample MR analysis were performed using inverse variance weighting (IVW) to ascertain the causal association between immune cells and the risk of breast 删除了: are